Phylogenomic reconstruction indicates mitochondrial ancestor was an energy parasite. - Zhang Wang; Martin Wu (PLoS ONE, 2014)
Reconstruction of mitochondrial ancestor has great impact on our understanding of the origin of mitochondria. Previous studies have largely focused on reconstructing the last common ancestor of all contemporary mitochondria (proto-mitochondria), but not on the more informative pre-mitochondria (the last common ancestor of mitochondria and their alphaproteobacterial sister clade). Using a phylogenomic approach and leveraging on the increased taxonomic sampling of alphaproteobacterial and eukaryotic genomes, we reconstructed the metabolisms of both proto-mitochondria and pre-mitochondria. Our reconstruction depicts a more streamlined proto-mitochondrion than these predicted by previous studies, and revealed several novel insights into the mitochondria-derived eukaryotic metabolisms including the lipid metabolism. Most strikingly, pre-mitochondrion was predicted to possess a plastid/parasite type of ATP/ADP translocase that imports ATP from the host, which posits pre-mitochondrion as an energy parasite that directly contrasts with the current role of mitochondria as the cell's energy producer. In addition, pre-mitochondrion was predicted to encode a large number of flagellar genes and several cytochrome oxidases functioning under low oxygen level, strongly supporting the previous finding that the mitochondrial ancestor was likely motile and capable of oxidative phosphorylation under microoxic condition.